Constructing stable vector bundles from curves with torsion normal bundle - Licanic, Sergio (MATHEMATICA SCANDINAVICA, 2023)
Given a smooth irreducible curve S with torsion normal bundle on a projective surface X, we provide a criterion for the non-emptiness of the moduli of slope stable vector bundles with prescribed Chern classes. The criterion is given in terms of the topology of the pair (X,S).